DEVELOPMENT OF IRRIGATION AND LAND RECLAMATION SYSTEMS IN THE UZBEK SSR (1945–1980) (Scientific journal of the Fergana State University, 2026)
In the post–World War II period, irrigated agriculture played a decisive role in the agricultural sector of the Uzbek Soviet Socialist Republic. This article analyzes the development of irrigation and land reclamation systems in the territory of the Uzbek SSR between 1945 and 1980. It highlights the importance and role of irrigated farming in the agrarian sector after the war. The study presents factual evidence showing that from 1945 to 1980, investments in irrigation infrastructure increased sharply, large hydraulic engineering structures were built, and the area of irrigated lands expanded several times. As a result, agricultural productivity grew, and the status of “white gold” – cotton monoculture – was strengthened.However, while the expansion of irrigation brought short-term economic success (such as increased yields and the development of new lands), in the long term it led to serious environmental problems — land salinization, the drying up of the Aral Sea, and the degradation of soil quality.